Pengaruh Celebrity Endorser dan Daya Tarik Iklan terhadap Minat Beli Ulang Shampo Pantene (Studi Kasus Kecamatan Padang Panjang Barat) - Eliza, Eliza; Mulya, Jumiatul (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2021)
This study aims to analyze the effect of celebrity endorsements and attractiveness of advertisements on consumers of Pantene shampoo in Padang Panjang Barat sub-district. The type of research used is quantitative associative research. The sample in this study were 100 respondents. The data analysis technique used is multiple linear regression. The results showed that 1) Celebrity endorsers had a significant positive effect on repurchase interest and 2) Ad attractiveness had a significant positive effect on repurchase interest. Based on the analysis that has been tested, the celebrity endorser and the attractiveness of advertising together affect the repurchase interest of Pantene shampoo consumers in West Padang Panjang District. The value of R2 is 0.563, so it can be concluded that the contribution of celebrity endorser influence and advertising attractiveness to repurchase interest is 56.3%.